Technical Discussion Paper on Concessional Insurance - World Bank Group (World Bank, Washington, DC, 2019)
Climate change, weather-related disasters, and slow-onset changes such as rising sea levels threaten sustainable development and force some 26 million people into poverty every year. Sovereign disaster risk insurance and other forms of risk finance, as part of a broader financial protection strategy, can help countries increase their financial resilience to disaster and climate shocks. This discussion paper aims to contribute to the ongoing discussions among development partners about the operationalization of premium subsidies for sovereign disaster risk insurance, the context of increasing interest among development partners in providing concessional finance, including premium subsidies. The paper draws on lessons from past and existing premium subsidy schemes, and from the World Bank’s operational experience on disaster risk financing and insurance (DRFI), including regional catastrophe risk pools. It aims to inform the dialogue on how to operationalize concessional insurance. The objective of the paper is not to provide specific recommendations, but rather to highlight key issues and options to be considered when operationalizing concessional insurance. This discussion paper builds on the World Bank Group’s cascade approach, which aims to crowd in private sector capital and markets to address the development challenges posed by disaster and climate shocks. Sovereign disaster risk insurance uses the capital of (re)insurance companies to transfer the financial cost of disaster response from client countries to the private investors. Furthermore, it utilizes private sector experience in designing appropriate risk financing solutions for clients.